1967
DOI: 10.1084/jem.126.4.539
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Malnutrition on the Inflammatory Response

Abstract: In the present experiments, Selye's granuloma pouch technique was applied to the study of the effect of host nutritional state on inflammation and the local tissue response. The normal response of well-nourished laboratory rats fed a diet containing 28% protein to the injection of 1% croton oil into a preformed subcutaneous air sac involved the accumulation of hemorrhagic exudate in the pouch lumen and the progressive thickening of the pouch wall, with the proliferation and maturation of fibroblasts and the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…2 Subsequently, Selye's granuloma pouch model was used to study other forms of immunomodulation, for example, by malnutrition and other noxae. 3 Another historical example of air pouch use was the isolation of a tumor angiogenesis factor (TAF) from Walker tumor-elicited ascitic fluid and the demonstration of its angiogenic effect in the rat dorsal air sac assay. 4 The first use of the air pouch model to study infection and inflammation was also a half century ago.…”
Section: Introductionmentioning
confidence: 99%
“…2 Subsequently, Selye's granuloma pouch model was used to study other forms of immunomodulation, for example, by malnutrition and other noxae. 3 Another historical example of air pouch use was the isolation of a tumor angiogenesis factor (TAF) from Walker tumor-elicited ascitic fluid and the demonstration of its angiogenic effect in the rat dorsal air sac assay. 4 The first use of the air pouch model to study infection and inflammation was also a half century ago.…”
Section: Introductionmentioning
confidence: 99%
“…Méndez et al subjected 10 male subjects to artificial hyperpyrexia simulating that used in the treatment of syphilis and observed a highly significant decrease in serum vitamin A levels, but no changes in the levels of carotene, vitamin E, alkaline phosphatase, riboflavin, or ascorbic acid [169]. Although most of INCAP's work on malnutrition and infection was in humans, very interesting papers by Taylor et al in 1967 and showed that an induced inflammatory response to croton oil in a granular pouch was reduced in rats on a low-protein diet [170,171].…”
Section: Miscellaneousmentioning
confidence: 99%
“…Maternal malnutrition during gestation and lactation may result in endocrine immune dysfunction in the hypothalamic-pituitary-adrenal axis, permanently altering the adrenocorticotrophic and glucocorticoid hormones concentration, which promote changes in the leptin levels during acute and chronic inflammations, contributing affecting the endocrine and immunologic systems (Barjafidalgo et al, 2003). Taylor et al (1967) studied the effects of intrauterine malnutrition on the intensity of inflammatory response and concluded that the reticuloendothelial system is depressed, lessening the quality with which macrophages are formed in various tissues. The local inflammatory response was greatly influenced by malnourishment; there was a delay in tissue repair in rats, as the nourished animals exudate presented fibroblasts with collagen deposits -which was not found in the malnourished animals exudate.…”
Section: Introductionmentioning
confidence: 99%